2016
DOI: 10.1039/c5tc04141d
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous generation of interlayers in OPVs with silver cathodes: enhancing Voc and lifetime

Abstract: A major contribution to the performance improvement of organic photovoltaic (OPV) devices is due to the successful engineering of the metal/organic interface by generating interlayers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
(45 reference statements)
0
24
0
Order By: Relevance
“…The self‐organization method not only simplifies the fabrication procedure significantly but also makes the tolerance of the interlayer to thickness variation no need consideration. And hence, intensive investigations have been focused on the self‐organization method in fullerene‐based OSCs …”
Section: Device Characteristics Using Pvp As Cil With Different Procementioning
confidence: 99%
See 2 more Smart Citations
“…The self‐organization method not only simplifies the fabrication procedure significantly but also makes the tolerance of the interlayer to thickness variation no need consideration. And hence, intensive investigations have been focused on the self‐organization method in fullerene‐based OSCs …”
Section: Device Characteristics Using Pvp As Cil With Different Procementioning
confidence: 99%
“…The self‐organization method is based on the self‐assembly of the interlayer material during the film deposition process, and many factors have been suggested to explain the origin of the migration of the interlayer materials. It has been demonstrated that when an interlayer material has higher surface energy and stronger interaction with the indium tin oxide (ITO) electrode, it may tend to migrate to the near ITO side, and vice versa . For instance, Wei et al introduced fluorocarbon chains to [6,6]‐phenyl‐C61‐butyric acid methyl ester (PC 61 BM) to decrease the surface energy of PC 61 BM, and as a result, the fluorinated PC 61 BM segregated to the top of the AL, forming the CIL and AL simultaneously .…”
Section: Device Characteristics Using Pvp As Cil With Different Procementioning
confidence: 99%
See 1 more Smart Citation
“…9 Among these, PEDOT:PSS exhibits the best electrical and optical properties [10][11][12][13][14] and is utilized in organic electronic devices such as organic light emitting diodes (OLEDs) 15 and organic photovoltaics (OPVs). 16 Therefore, it is considered as a potential organic electronic material.…”
Section: Introductionmentioning
confidence: 99%
“…S6 (ESI †) shows the XPS spectra of C 1s and S 2p of P3HT:bis-PC 61 BM blend films with different concentrations of piperazine. As seen here, the C 1s peak can be fitted into two components, corresponding to C-C at 284.78 eV and C-O at 285.91 eV, 39 where the C-O signal can be assigned to the component of bis-PC 61 BM. Fig.…”
Section: Stability Improvement By Inserting a Thin C 60 Layermentioning
confidence: 82%